Multisensory contributions to skin‐cosmetic product interactions - Spence, C; Zhang, T (Wiley, 2024)
The human face is one of the most salient regions of the body surface. Ratings of facial attractiveness, as well as judgements of a person's age, are influenced by the appearance of facial skin (not to mention the presence/absence of wrinkles). Unsurprisingly, many consumers spend huge amounts of money on trying to protect, maintain, and/or enhance their facial appearance. As highlighted by the evidence presented in this narrative review, both the skin and the cosmetic products that many consumers use are fundamentally multisensory in nature. The complex interaction between the particular skin site stimulated and the multisensory attributes of the product (e.g., when it is applied) can exert a number of effects on an individual's mood, their emotions, as well as on their self‐perception (and self‐confidence), over‐and‐above any functional effects that the cream or lotion may have on the skin itself. In this narrative historical review, the literature on the multisensory perception of facial skin is summarized and critically evaluated. Multisensory interactions taking place between the cosmetic product, its packaging, as well as its use/application at the sensory, cognitive, and emotional levels are all discussed.